Mensuração do nível de desempenho de projetos de geração de energia fotovoltaica para comercialização de energia - Thomasi, Virginia (2021)
Sustainable electricity production can be achieved through incentives for generation from a renewable source. Brazil has been promoting the generation of electricity from renewable sources through auctions. Energy auctions aim to increase competitiveness between generators and between distributors. In such a context, photovoltaics offers increasingly competitive prices and lower than other renewable sources. Given this scenario, entrepreneurs and investors when starting the process of preparing projects need to observe the factors that influence construction and implementation. Since the electricity sector is complex and there are no simple solutions to most structural problems. The growth of the market depends not only on external incentives but also on searches for alternatives that boost the sector. Based on this, the objective of this study is to build a model to measure the performance level of photovoltaic power plant projects for the commercialization of energy in the regulated contracting environment. The diagnosis was designed through a performance measurement system based on Critical Success Factors, obtained from a systematic review process and Fuzzy Delphi Method with the participation of 10 energy specialists. These factors were grouped into three Fundamental Points of View: Economic, Local, and Technological. From this, performance indicators were constructed in order to calculate the Project Performance Index. A case study was applied to a project of a photovoltaic power plant with a power of 10 MW and with construction not started. As a result, the mathematical formulation was able to weigh the indicators and measure the performance of the project. The main contributions of the study deal with the identification of critical success factors and the measurement methodology developed for the performance diagnosis model. It can serve to identify the indicators that still need improvements in the planning process. Known the fundamental factors for the implementation of a photovoltaic power generation project, actions can be taken to increase the participation of these projects in the Brazilian electric matrix.